MODAL KERJA, ASET DAN SUKU BUNGA TERHADAP PERUBAHAN LABA PADA PT. SANFREMY PRATAMA MEDAN - Magdalena Judika Br Siringoringo; Mardiah Hasanah Nasution; Edy Firmansyah; Sunday Ade Sitorus; Petrus Loo; SUNDAY ADE SITORUS (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted at PT.Sanfremy Pratama Medan engaged in the distributor of Engineering Equipment and Civil Construction Test Equipment. The purpose of this study was to determine and analyze the effect of Working Capital, Assets and Interest Rates on Changes in Profit at PT. Sanfremy Pratama Medan. The data analysis technique used in this research is quantitative research. The population in this study is PT. Sanfremy Pratama Medan from January 2014 to December 2018 so that the total population in this study is 12 x 5 years = 60 data. The sample is 12 months x 5 years = 60 data. In this study all the population was sampled, where the sampling methodology used the saturated sample methodology. The data collection technique used is documentation for research data. Variables are measured by the ratio scale. The results of the study prove that working capital has no effect and is significant on profit changes at PT. Sanfremy Pratama Medan. Assets and significant effect on changes in profit at PT. Sanfremy Pratama Medan. Interest rates have no effect and are not significant to changes in profit at PT. Sanfremy Pratama Medan. Working capital, assets and interest rates have a significant and significant effect on changes in profit at PT. Sanfremy Pratama Medan.